Structure–activity relationship study of 4-(thiazol-5-yl)benzoic acid derivatives as potent protein kinase CK2 inhibitors. Issue 5 (1st March 2016) - Ohno, Hiroaki; Minamiguchi, Daiki; Nakamura, Shinya; Shu, Keito; Okazaki, Shiho; Honda, Maho; Misu, Ryosuke; Moriwaki, Hirotomo; Nakanishi, Shinsuke; Oishi, Shinya; Kinoshita, Takayoshi; Nakanishi, Isao; et al.
Graphical abstract: Abstract: Two classes of modified analogs of 4-(thiazol-5-yl)benzoic acid-type CK2 inhibitors were designed. The azabenzene analogs, pyridine- and pyridazine-carboxylic acid derivatives, showed potent protein kinase CK2 inhibitory activities [IC50 (CK2α) = 0.014–0.017 μM; IC50 (CK2α′) = 0.0046–0.010 μM]. Introduction of a 2-halo- or 2-methoxy-benzyloxy group at the 3-position of the benzoic acid moiety maintained the potent CK2 inhibitory activities [IC50 (CK2α) = 0.014–0.016 μM; IC50 (CK2α′) = 0.0088–0.014 μM] and led to antiproliferative activities [CC50 (A549) = 1.5–3.3 μM] three to six times higher than those of the parent compound.